Effect of Powder Metallurgy Copper Electrode on Surface Modification of Mild Steel - Izzat Shakri, Muhammad Amin; Liew, Pay Jun; Wang, Jingsi (Semarak International Journal of Material Research, 2025)
Mild steel, widely used for its ductility, weldability, and cost-effectiveness, suffers from low corrosion and wear resistance. This study aims to enhance these properties by applying surface modification using electrical discharge coating (EDC) with powder metallurgy (PM) copper electrodes. The impact of varying compaction pressures and sintering temperatures on the microhardness and thickness of the deposited layer were examined. The results showed that maximum hardness can be obtained at 650°C and 3 tons, while maximum coating layer thickness was 12.5 μm at 550°C and 5 tons. Higher pressure generally reduces copper weight % and higher sintering temperature enhances the microhardness of the mild steel.